Preparation method of heat-conducting polyethylene composite material, flame-retardant dynamic cross-linking agent and preparation method of flame-retardant dynamic cross-linking agent
By adding dynamic crosslinking agent with flame retardant function to thermally conductive polyethylene composite materials and introducing reversible covalent bonds, the problem of polyethylene cable sheath is prone to heat and combustion, and the recycling of materials is realized, improving the Flame retardant efficiency and recycling.
Patent Information
- Application Number
- CN202411482838.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-18
AI Technical Summary
The existing polyethylene cable sheath material is prone to heat and burn during power-on operation, resulting in fire accidents, and it is difficult to recycle and reuse the cross-linked polyethylene.
By adding a dynamic crosslinking agent with flame retardant function, the transesterification reaction of boric acid lipo is introduced into the thermally conductive composite material, and reversible covalent bonds are introduced to impart the characteristics of the thermosetting material, and the chemical bonds are activated by heating to realize the thermosetting material to the thermoplastic material. The transformation of material separation, recycling and reuse is achieved, while improving the flame retardant efficiency of thermally conductive polyethylene composite materials.
The high-efficiency flame retardant of thermally conductive polyethylene composite materials and the recycling of materials are realized, and the flame retardant efficiency and recycling of materials are improved.
Smart Images

Figure CN119463399A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of polyethylene composite materials, and in particular to a preparation method of a thermally conductive polyethylene composite material, a flame retardant dynamic crosslinking agent and a preparation method thereof. Background Art
[0002] Polyethylene is a thermoplastic resin obtained by polymerization of ethylene monomers, which has the advantages of corrosion resistance and electrical insulation. Pure polyethylene has low temperature resistance and is difficult to use as a cable sheath material. However, cross-linked polyethylene not only has greatly improved mechanical properties, environmental stress cracking resistance and creep resistance, but also greatly improved temperature resistance, so it is widely used in the field of cable sheaths.
[0003] As we all know, cables are prone to heat up and burn during power-on operation, which can lead to fire accidents. Therefore, cable sheath materials must have flame retardant properties. In the prior art, thermal conductive fillers are added to improve the thermal conductivity of polyethylene cable sheath materials, thereby reducing fire accidents caused by cable heating.
[0004] Another disadvantage of cross-linked polyethylene is that it is difficult to recycle and reuse the cross-linked polyethylene. Summary of the invention
[0005] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing a thermally conductive polyethylene composite material. By adding the dynamic cross-linking agent with flame retardant function of the present invention, the ester exchange reaction of boric acid ester is introduced into the thermally conductive composite material. The introduction of reversible covalent bonds not only gives the material the characteristics of traditional thermosetting materials, but also can activate chemical bonds by heating to achieve the transformation of thermosetting materials to thermoplastic materials, realize material separation, recycling and reuse, and at the same time improve the flame retardant efficiency of the thermally conductive polyethylene composite material.
[0006] Another object of the present invention is to provide a method for preparing a flame retardant dynamic crosslinking agent.
[0007] Another object of the present invention is to provide a flame retardant dynamic crosslinking agent.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] The invention provides a method for preparing a thermally conductive polyethylene composite material. Maleic anhydride grafted polyethylene, a flame retardant dynamic crosslinking agent and a thermally conductive filler are mixed and then pressed to obtain the thermally conductive polyethylene composite material. The addition amount of the flame retardant dynamic crosslinking agent is 2% to 5wt% of the maleic anhydride grafted polyethylene, and the optimal amount is 2wt%. The addition amount of the thermally conductive filler is 15 to 30wt% of the maleic anhydride grafted polyethylene, and the optimal amount is 30wt%.
[0010] The preparation of the flame retardant dynamic crosslinking agent is as follows:
[0011] The dihydroxyethylamine derivative and the phenylboronic acid derivative are dissolved in an anhydrous solvent at a molar ratio of 1:(0.8-1.2), and reacted under a nitrogen atmosphere to obtain a phenylboronic acid ester derivative; then, diisocyanate is added to continue the reaction, and the solvent is removed by rotary evaporation to obtain a flame retardant dynamic crosslinking agent.
[0012] Preferably, the reaction under a nitrogen atmosphere is specifically: reacting at 30°C to 60°C for 1 to 6 hours, and optimally at 50°C for 4 hours.
[0013] Preferably, the dihydroxyethylamine derivative is at least one of N,N-di(2-hydroxyethyl)ethylenediamine, diethanolamine, and triethanolamine, and the best is N,N-di(2-hydroxyethyl)ethylenediamine; the diisocyanate is one or two of hexamethylene diisocyanate, 2,4-diisocyanato-1-methylbenzene, and diphenylmethane diisocyanate, and the best is hexamethylene diisocyanate; the phenylboronic acid derivative is one or a combination of 4-aminomethylphenylboronic acid, 4-hydroxymethylphenylboronic acid, etc., and the best is 4-aminomethylphenylboronic acid; the solvent includes toluene, acetone, and N,N-dimethylformamide, and the best is N,N-dimethylformamide;
[0014] Preferably, the thermally conductive filler is an organically modified boron nitride nanosheet, and the preparation method thereof is as follows:
[0015] Hexagonal boron nitride is dispersed in a NaOH aqueous solution to prepare a hexagonal boron nitride dispersion; the hexagonal boron nitride dispersion is placed in a ball mill, ball-milled into hydroxylated boron nitride nanosheets, and washed with deionized water until neutral; the hydroxylated boron nitride nanosheets are ultrasonically dispersed in ethanol to prepare an ethanol dispersion of hydroxylated boron nitride nanosheets, and then a coupling agent is added, stirred at 60°C to 90°C for 2 to 6 hours, washed with ethanol, filtered, and dried to obtain organically modified boron nitride nanosheets.
[0016] Preferably, the concentration of the hexagonal boron nitride dispersion is 0.2-0.5 g / mL, preferably 0.5 g / mL; the concentration of the ethanol dispersion of the hydroxylated boron nitride nanosheets is 0.1-0.2 g / mL, preferably 0.1 g / mL.
[0017] Preferably, the coupling agent is at least one of γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, and titanate coupling agent, and the optimal coupling agent is KH-550 coupling agent; the addition amount of the coupling agent is 1.2-2.0wt% of the hydroxylated boron nitride nanosheets, and the optimal addition amount is 2.0wt%.
[0018] Preferably, the ultrasonic power is 70-90W, the ultrasonic time is 5-7h, the optimal temperature is 80°C, the stirring time is 2-6h, and the optimal time is 5h; the stirring rate is 300-600rpm / min; and the drying is carried out in a vacuum oven at 70-90°C for 4-5h.
[0019] Preferably, the maleic anhydride grafted polyethylene, the flame retardant dynamic crosslinking agent and the thermal conductive filler are mixed and then pressed, specifically:
[0020] The maleic anhydride grafted polyethylene, the flame retardant dynamic crosslinking agent and the thermal conductive filler are added to a double-roll open mill with a front roller temperature of 98-102°C and a rear roller temperature of 103-107°C, and mixed for 1.5-2.5 hours at a front roller speed of 8-12rpm and a rear roller speed of 8-12rpm; finally, pressed in a tablet press at 125-135°C and 5-7MPa for 25-35min; more preferably, the maleic anhydride grafted polyethylene, the flame retardant dynamic crosslinking agent and the thermal conductive filler are added to a double-roll open mill with a front roller temperature of 100°C and a rear roller temperature of 105°C, and mixed for 2 hours at a front roller speed of 10rpm and a rear roller speed of 10rpm; finally, pressed in a tablet press at 130°C and 6MPa for 30min.
[0021] The present invention also provides a method for preparing a flame retardant dynamic crosslinking agent, comprising the following steps:
[0022] The dihydroxyethylamine derivative and the phenylboronic acid derivative are dissolved in an anhydrous solvent at a molar ratio of 1:(0.8-1.2), and reacted at 30°C-60°C for 1-6 hours under a nitrogen atmosphere to obtain a phenylboronic acid ester derivative; then, diisocyanate is added to continue the reaction, and the solvent is removed by rotary evaporation to obtain a flame retardant dynamic crosslinking agent; more preferably, the dihydroxyethylamine derivative and the phenylboronic acid derivative are dissolved in a molar ratio of 1:1, the reaction temperature is 50°C, and the reaction time is 4 hours.
[0023] The dihydroxyethylamine derivative is at least one of N,N-di(2-hydroxyethyl)ethylenediamine, diethanolamine, and triethanolamine; the phenylboric acid derivative is at least one of 4-aminomethylphenylboric acid and 4-hydroxymethylphenylboric acid; and the diisocyanate is one or two of hexamethylene diisocyanate, 2,4-diisocyanato-1-methylbenzene, and diphenylmethane diisocyanate.
[0024] The invention also provides a flame retardant dynamic crosslinking agent, which is prepared by the preparation method of the flame retardant dynamic crosslinking agent.
[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0026] (1) The preparation method of the thermally conductive polyethylene composite material of the present invention introduces the ester exchange reaction of boric acid ester into the thermally conductive composite material by adding the dynamic cross-linking agent with flame retardant function of the present invention. The introduction of reversible covalent bonds not only gives the material the characteristics of traditional thermosetting materials, but also can activate chemical bonds by heating to achieve the transformation of thermosetting materials into thermoplastic materials, realize material separation, recycling and reuse, and give the PE component and h-BN in the thermally conductive composite material the ability to be recycled.
[0027] (2) The preparation method of the thermally conductive polyethylene composite material of the present invention ball-mills hexagonal boron nitride h-BN into boron nitride nanosheets BNNS and performs silanization modification, which not only improves the thermal conductivity per unit mass of h-BN, but also effectively reduces the interface thermal resistance between the thermally conductive filler and the matrix resin. At the same time, h-BN has good insulation and thermal stability. Adding this thermally conductive filler can improve the electrical insulation performance and thermal stability of the composite matrix.
[0028] (3) The flame retardant dynamic crosslinking agent of the present invention is rich in boron and nitrogen elements. When boron and nitrogen are used together, they can play a role in the condensed phase and gas phase during the combustion process, and can obtain a synergistic effect to improve the flame retardant efficiency. The present invention introduces boric acid ester into the cable material, which can play the flame retardant role of the boric acid ester condensed phase and reduce the amount of flame retardant added; at the same time, the flame retardant is added to the polyethylene matrix in the form of a crosslinking agent, which inhibits the migration of the flame retardant. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The present invention provides a synthetic process of a flame retardant dynamic cross-linking agent according to an embodiment of the present invention.
[0030] Figure 2 The figure shows the preparation process of silanized boron nitride nanosheets f-BNNS according to an embodiment of the present invention.
[0031] Figure 3 Schematic diagram of the structure of the f-BNNS / cross-linked polyethylene composite material of an embodiment of the present invention. DETAILED DESCRIPTION
[0032] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0033] In the following examples, the sample preparation methods for various performance tests are as follows:
[0034] The material extruded from the double-roll mill was cooled and formed, and then dried in a blast oven at 90°C for 12 hours to remove moisture. The f-BNNS / cross-linked polyethylene composite material was pressed into test specimens of different sizes, such as 125mm×3mm×1.6mm (tensile properties), 125mm×3mm×1.6mm (vertical combustion) and 30mm×30mm×2mm (thermal conductivity). The parameters of the press were hot pressing temperature of 130°C, hot pressing pressure of 6MPa, and hot pressing time of 30min.
[0035] Example 1
[0036] (1) Figure 1 As shown, the preparation process of the dynamic flame retardant crosslinking agent is as follows:
[0037] 14.82g of N,N-di(2-hydroxyethyl)ethylenediamine and 15.10g of 4-aminomethylphenylboronic acid were dissolved in N,N-dimethylformamide and reacted for 6h under nitrogen atmosphere at 60°C. Then 33.64g of hexamethylene diisocyanate was added and the reaction continued for 4h. The dynamic flame retardant crosslinking agent FBDC was obtained after the solvent was removed by rotary evaporation at 70°C.
[0038] (2) Figure 2 As shown, the preparation method of silanized boron nitride nanosheets f-BNNS is as follows:
[0039] 20.00g of hexagonal boron nitride h-BN was dispersed in 40mL of 10mol / L NaOH aqueous solution to prepare a h-BN dispersion of a certain concentration. The h-BN dispersion was placed in a ball mill, ball-milled into hydroxylated boron nitride nanosheets BNNS-OH, and washed with deionized water to pH = 7. 6g of BNNS-OH was ultrasonically dispersed in 60mL of ethanol to prepare a BNNS-OH / ethanol dispersion, wherein the power of the ultrasonic machine was 80W and the ultrasonic time was 6h. 0.12g of silane coupling agent KH-550 was added to the BNNS-OH / ethanol dispersion, stirred at high speed at 80℃ for 5h, washed with ethanol, and filtered to obtain organically modified f-BNNS.
[0040] (3) The preparation method of f-BNNS / cross-linked polyethylene composite material is as follows:
[0041] The organic modified f-BNNS was pre-dried in a vacuum oven at 80°C for 4h, 100g of maleic anhydride grafted polyethylene, 2g of FDBC, and 30g of organic modified f-BNNS were weighed and added to a two-roll open mill with a front roller temperature of 100°C and a rear roller temperature of 105°C, and mixed for 2h at a front roller speed of 10rpm and a rear roller speed of 10rpm. Finally, the polyethylene thermal conductive composite material was obtained by pressing in a tablet press at 130°C and 6MPa for 30min. The structure of the f-BNNS / cross-linked polyethylene composite material is shown in FIG. Figure 3 shown.
[0042] (4) The reprocessing operation of f-BNNS / cross-linked polyethylene composites is as follows:
[0043] 80 g of the composite material was crushed in a crusher, the crushed particles were passed through a 100-mesh sieve, 50 g of the crushed material was pressed in a tablet press at 130° C. and 6 MPa for 30 min to obtain a recycled polyethylene thermal conductive composite material.
[0044] Example 2
[0045] (1) The preparation method of the dynamic flame retardant crosslinking agent is as follows:
[0046] 10.52 g of diethanolamine and 15.10 g of 4-aminomethylphenylboronic acid were dissolved in N,N-dimethylformamide, and reacted at 50°C for 6 h in a nitrogen atmosphere. Then, 33.64 g of hexamethylene diisocyanate was added and the reaction was continued for 4 h. The dynamic flame retardant crosslinking agent FBDC was obtained after removing the solvent by rotary evaporation at 70°C.
[0047] (2) The preparation method of silanized boron nitride nanosheets f-BNNS is as follows:
[0048] The preparation method of the silanized boron nitride nanosheets f-BNNS is the same as that in Example 1.
[0049] (3) The preparation method of f-BNNS / cross-linked polyethylene composite material is as follows:
[0050] The organic modified f-BNNS was pre-dried in a vacuum oven at 80°C for 4h, and 100g of maleic anhydride grafted polyethylene, 2g of FDBC, and 20g of organic modified f-BNNS were weighed and added to a two-roll open mill with a front roller temperature of 100°C and a rear roller temperature of 105°C, and mixed for 2h at a front roller speed of 10rpm and a rear roller speed of 10rpm. Finally, the polyethylene thermal conductive composite material was pressed in a tablet press at 130°C and 6MPa for 30min.
[0051] (4) Preparation of f-BNNS / cross-linked polyethylene composite recycled materials is as follows:
[0052] The preparation of the recycled material is the same as the steps in Example 1.
[0053] Example 3
[0054] (1) The preparation method of the dynamic flame retardant crosslinking agent is as follows:
[0055] 14.82g of N,N-di(2-hydroxyethyl)ethylenediamine and 15.10g of 4-aminomethylphenylboronic acid were dissolved in N,N-dimethylformamide and reacted for 6h under nitrogen atmosphere at 60°C. Then 34.84g of 2,4-diisocyanato-1-methylbenzene was added and the reaction continued for 4h. The dynamic flame retardant crosslinking agent FBDC was obtained after the solvent was removed by rotary evaporation at 70°C.
[0056] (2) The preparation method of silanized boron nitride nanosheets f-BNNS is as follows:
[0057] The preparation method of the silanized boron nitride nanosheets f-BNNS is the same as that in Example 1.
[0058] (3) The preparation method of f-BNNS / cross-linked polyethylene composite material is as follows:
[0059] The organic modified f-BNNS was pre-dried in a vacuum oven at 80°C for 4h, and 100g of maleic anhydride grafted polyethylene, 2g of FDBC, and 30g of organic modified f-BNNS were weighed and added to a two-roll open mill with a front roller temperature of 100°C and a rear roller temperature of 105°C, and mixed for 2h at a front roller speed of 10rpm and a rear roller speed of 10rpm. Finally, the polyethylene thermal conductive composite material was pressed in a tablet press at 130°C and 6MPa for 30min.
[0060] (4) Preparation of f-BNNS / cross-linked polyethylene composite recycled materials is as follows:
[0061] The preparation of the recycled material is the same as the steps in Example 1.
[0062] Example 4
[0063] 10.52 g of diethanolamine and 15.10 g of 4-aminomethylphenylboronic acid were dissolved in N,N-dimethylformamide, and reacted at 50°C for 6 h in a nitrogen atmosphere. Then, 34.84 g of 2,4-diisocyanato-1-methylbenzene was added and the reaction was continued for 4 h. The dynamic flame retardant crosslinking agent FBDC was obtained after removing the solvent by rotary evaporation at 70°C.
[0064] (2) The preparation method of silanized boron nitride nanosheets f-BNNS is as follows:
[0065] The preparation method of the silanized boron nitride nanosheets f-BNNS is the same as that in Example 1.
[0066] (3) The preparation method of f-BNNS / cross-linked polyethylene composite material is as follows:
[0067] The organic modified f-BNNS was pre-dried in a vacuum oven at 80°C for 4h, and 100g of maleic anhydride grafted polyethylene, 2g of FDBC, and 20g of organic modified f-BNNS were weighed and added to a two-roll open mill with a front roller temperature of 100°C and a rear roller temperature of 105°C, and mixed for 2h at a front roller speed of 10rpm and a rear roller speed of 10rpm. Finally, the polyethylene thermal conductive composite material was pressed in a tablet press at 130°C and 6MPa for 30min.
[0068] (4) Preparation of f-BNNS / cross-linked polyethylene composite recycled materials is as follows:
[0069] The preparation of the recycled material is the same as the steps in Example 1.
[0070] Example 5
[0071] 14.82g of N,N-di(2-hydroxyethyl)ethylenediamine and 15.10g of 4-aminomethylphenylboronic acid were dissolved in N,N-dimethylformamide and reacted for 6h under nitrogen atmosphere at 60°C. Then, 50.05g of diphenylmethane diisocyanate was added and the reaction continued for 4h. The dynamic flame retardant crosslinking agent FBDC was obtained after the solvent was removed by rotary evaporation at 70°C.
[0072] (2) The preparation method of silanized boron nitride nanosheets f-BNNS is as follows:
[0073] The preparation method of the silanized boron nitride nanosheets f-BNNS is the same as that in Example 1.
[0074] (3) The preparation method of f-BNNS / cross-linked polyethylene composite material is as follows:
[0075] The organic modified f-BNNS was pre-dried in a vacuum oven at 80°C for 4h, and 100g of maleic anhydride grafted polyethylene, 2g of FDBC, and 30g of organic modified f-BNNS were weighed and added to a two-roll open mill with a front roller temperature of 100°C and a rear roller temperature of 105°C, and mixed for 2h at a front roller speed of 10rpm and a rear roller speed of 10rpm. Finally, the polyethylene thermal conductive composite material was pressed in a tablet press at 130°C and 6MPa for 30min.
[0076] (4) Preparation of f-BNNS / cross-linked polyethylene composite recycled materials is as follows:
[0077] The preparation of the recycled material is the same as the steps in Example 1.
[0078] Example 6
[0079] 10.52 g of diethanolamine and 15.10 g of 4-aminomethylphenylboronic acid were dissolved in N,N-dimethylformamide, and reacted at 50°C for 6 h in a nitrogen atmosphere. Then, 50.05 g of diphenylmethane diisocyanate was added and the reaction was continued for 4 h. The dynamic flame retardant crosslinking agent FBDC was obtained after removing the solvent by rotary evaporation at 70°C.
[0080] (2) The preparation method of silanized boron nitride nanosheets f-BNNS is as follows:
[0081] The preparation method of the silanized boron nitride nanosheets f-BNNS is the same as that in Example 1.
[0082] (3) The preparation method of f-BNNS / cross-linked polyethylene composite material is as follows:
[0083] The organic modified f-BNNS was pre-dried in a vacuum oven at 80°C for 4h, and 100g of maleic anhydride grafted polyethylene, 2g of FDBC, and 20g of organic modified f-BNNS were weighed and added to a two-roll open mill with a front roller temperature of 100°C and a rear roller temperature of 105°C, and mixed for 2h at a front roller speed of 10rpm and a rear roller speed of 10rpm. Finally, the polyethylene thermal conductive composite material was pressed in a tablet press at 130°C and 6MPa for 30min.
[0084] (4) Preparation of f-BNNS / cross-linked polyethylene composite recycled materials is as follows:
[0085] The preparation of the recycled material is the same as the steps in Example 1.
[0086] Comparative Example 1
[0087] The hexagonal boron nitride h-BN was pre-dried in a vacuum oven at 80°C for 4 hours, and 100g of maleic anhydride grafted polyethylene, 2g of hexamethylene diisocyanate, and 30g of hexagonal boron nitride h-BN were weighed and added to a two-roll open mill with a front roller temperature of 100°C and a rear roller temperature of 105°C, and mixed for 2 hours at a front roller speed of 10rpm and a rear roller speed of 10rpm. Finally, the polyethylene thermal conductive composite material was pressed in a tablet press at 130°C and 6MPa for 30 minutes.
[0088] 80 g of the composite material was crushed in a crusher, the crushed particles were passed through a 100-mesh sieve, 50 g of the crushed material was pressed in a tablet press at 130° C. and 6 MPa for 30 min to obtain a recycled polyethylene thermal conductive composite material.
[0089] Performance Test Results
[0090] Performance test: refer to national standards "GB / T 1040 Determination of tensile properties", "GB 2409-84 Vertical combustion method" and "ISO 22007-2 Transient plane heat source method".
[0091] Tensile property test: A sample of 125 mm × 3 mm × 1.6 mm was clamped on a tensile testing machine using a clamp, and the tensile strength and elongation at break of the sample were read by the tensile testing machine.
[0092] Vertical combustion test: Prepare a sample strip of 125mm×3mm×1.6mm. The distance between the top of the burner and the bottom of the sample is 10mm. Record the time from the flame to the flame extinguishing after two exposures and withdrawals to determine the flame retardant performance level.
[0093] Thermal conductivity test: Prepare a disc with a diameter of 30 mm and a thickness of 2 mm, place the sample in a Hot Disk thermal constant analyzer, apply a certain heat flow, measure the temperature change at different positions, and calculate the thermal conductivity of the material.
[0094] Table 1 Properties of the composite materials (A) and after reprocessing (B) of Examples 1 to 6 and Comparative Example 1
[0095]
[0096] The composite material in Comparative Example 1 could not be formed after being crushed and hot pressed.
[0097] It can be seen from the above examples that by adding the flame retardant dynamic crosslinking agent provided by the present invention, the flame retardant polyethylene composite material prepared has good tensile strength, flame retardant properties and thermal conductivity, which can reach up to 26.5MPa, reaching the V-0 grade, and the thermal conductivity reaches 1.6W / m·K. In addition, the flame retardant dynamic crosslinking agent provided by the present invention enables the polyethylene composite material to be effectively recycled.
[0098] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a thermally conductive polyethylene composite material, characterized in that: The maleic anhydride grafted polyethylene, the flame retardant dynamic crosslinking agent and the thermal conductive filler are mixed and pressed to obtain a thermal conductive polyethylene composite material; the addition amount of the flame retardant dynamic crosslinking agent is 2% to 5wt% of the maleic anhydride grafted polyethylene; the addition amount of the thermal conductive filler is 15 to 30wt% of the maleic anhydride grafted polyethylene; The preparation of the flame retardant dynamic crosslinking agent is as follows: The dihydroxyethylamine derivative and the phenylboronic acid derivative are dissolved in an anhydrous solvent at a molar ratio of 1:(0.8-1.2), and reacted under a nitrogen atmosphere to obtain a phenylboronic acid ester derivative; then, diisocyanate is added to continue the reaction, and the solvent is removed by rotary evaporation to obtain a flame retardant dynamic crosslinking agent.
2. The method for preparing the thermally conductive polyethylene composite material according to claim 1, characterized in that: The reacting under a nitrogen atmosphere is specifically: reacting under a nitrogen atmosphere at 30° C. to 60° C. for 1 to 6 hours.
3. The method for preparing the thermally conductive polyethylene composite material according to claim 1, characterized in that: The dihydroxyethylamine derivative is at least one of N,N-di(2-hydroxyethyl)ethylenediamine, diethanolamine, and triethanolamine; the phenylboric acid derivative is at least one of 4-aminomethylphenylboric acid and 4-hydroxymethylphenylboric acid; and the diisocyanate is one or two of hexamethylene diisocyanate, 2,4-diisocyanato-1-methylbenzene, and diphenylmethane diisocyanate.
4. The method for preparing the thermally conductive polyethylene composite material according to claim 1, characterized in that: The thermal conductive filler is an organically modified boron nitride nanosheet, and the preparation method thereof is as follows: Hexagonal boron nitride is dispersed in a NaOH aqueous solution to prepare a hexagonal boron nitride dispersion; the hexagonal boron nitride dispersion is placed in a ball mill, ball-milled into hydroxylated boron nitride nanosheets, and washed with deionized water until neutral; the hydroxylated boron nitride nanosheets are ultrasonically dispersed in ethanol to prepare an ethanol dispersion of hydroxylated boron nitride nanosheets, and then a coupling agent is added, stirred at 60°C to 90°C for 2 to 6 hours, washed with ethanol, filtered, and dried to obtain organically modified boron nitride nanosheets.
5. The method for preparing the thermally conductive polyethylene composite material according to claim 4, characterized in that: The concentration of the hexagonal boron nitride dispersion is 0.2-0.5 g / mL; the concentration of the ethanol dispersion of the hydroxylated boron nitride nanosheets is 0.1-0.2 g / mL.
6. The method for preparing the thermally conductive polyethylene composite material according to claim 4, characterized in that: The coupling agent is at least one of γ-aminopropyltriethoxysilane, vinyltrimethoxysilane and titanate coupling agent; the added amount of the coupling agent is 1.2-2.0wt% of the hydroxylated boron nitride nanosheets.
7. The method for preparing the thermally conductive polyethylene composite material according to claim 4, characterized in that: The power of the ultrasound is 70-90W, and the ultrasound time is 5-7h; the stirring rate is 300-600rpm / min; and the drying is carried out in a vacuum oven at 70-90°C for 4-5h.
8. The method for preparing the thermally conductive polyethylene composite material according to claim 1, characterized in that: The maleic anhydride grafted polyethylene, the flame retardant dynamic crosslinking agent and the thermal conductive filler are mixed and then pressed, specifically: Maleic anhydride grafted polyethylene, flame retardant dynamic crosslinking agent and thermal conductive filler are added to a double-roll open mill with a front roller temperature of 98-102°C and a rear roller temperature of 103-107°C, and mixed for 1.5-2.5 hours at a front roller speed of 8-12 rpm and a rear roller speed of 8-12 rpm; finally, pressed in a tablet press at 125-135°C and 5-7 MPa for 25-35 minutes.
9. A method for preparing a flame retardant dynamic crosslinking agent, characterized in that: The following steps are involved: Dissolve a dihydroxyethylamine derivative and a phenylboronic acid derivative in an anhydrous solvent at a molar ratio of 1:(0.8-1.2), react at 30°C-60°C for 1-6 hours under a nitrogen atmosphere to obtain a phenylboronic acid ester derivative; then add diisocyanate to continue the reaction, and remove the solvent by rotary evaporation to obtain a flame retardant dynamic crosslinking agent; The dihydroxyethylamine derivative is at least one of N,N-di(2-hydroxyethyl)ethylenediamine, diethanolamine, and triethanolamine; the phenylboric acid derivative is at least one of 4-aminomethylphenylboric acid and 4-hydroxymethylphenylboric acid; and the diisocyanate is one or two of hexamethylene diisocyanate, 2,4-diisocyanato-1-methylbenzene, and diphenylmethane diisocyanate.
10. A flame retardant dynamic crosslinking agent, characterized in that: The flame retardant dynamic crosslinking agent is prepared by the preparation method of the flame retardant dynamic crosslinking agent according to claim 9.